At their own game - Zafiro, Frank (CreateSpace], 2014)
Jake Stankovic has been flying below the radar for years, dealing safely in stolen property crime with his two-man crew. But times are tough, so he decides to step up to the big money with a drug deal. Everything that can go wrong, does. The deal goes bad, a vengeful detective sets his sights on Jake, one of his crew might be a turncoat, and a woman from a long past affair suddenly reappears. The woman is the detective's ex-wife. And Jake used to be a cop.